The grammatical analysis of the interrogative ‘ Anna’ and its connotations in the Holy Qur’an An analytical descriptive study (Journal of Human Sciences, 2022)
The study of ‘ Anna’  is usually done in two chapters of Arabic grammar books which are: condition and interrogative. In this paper,  its position in the Holly Qur’an was tracked , and  the results showed  that  it was used only once  as condition and that what Arab scholars assured. For this reason the researcher focused on the interrogative ‘ ‘Anna’ and she used the  analytical method  for this study in order to know its properties and its contextual connotations in the Holly Qur’an. The research was divided into two parts; the first was a theoretical study about the interrogative ‘ Anna’. This part started by defining the interrogative and mentioning its famous words and its rhetorical purposes.  Also, it aimed to study ‘Anna’ and its meaning and its grammatical analysis in order to analyze its sentence anywhere in the  Holly Qur’an, and to present scholars’ points of views about its grammatical analysis in the second part of this paper. The results showed that ‘Anna’ was  used  for  the figurative question   in most  of its positions in the Holy Quran for the contextual  rhetorical purposes; and  It’s sentence system was limited  only to three patterns.  The  context  also referred  that it  has a general indication which used  to express something that has different aspects. Based on the results, the researcher suggested that ‘Anna’ should be analyzed as an adverb  to achieve the compatibility between its grammatical and  connotation function  in the context, and to bridge any shortcoming might affect  the meaning as it  was presented before. At the end, the  results and the recommendations of the research were presented.